PENGARUH KEPUASAN KERJA, MOTIVASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA SEKOLAH TINGGI AGAMA ISLAM NEGERI BATUSANGKAR - Hermayulis Syam (IAIN Batusangkar, 2016)
Effect of Job Satisfaction, Motivation and Leadership Styles Of Employee Performance in Sekolah Tinggi Agama Islam Negeri Batusanggkar. Issues raised in this study is whether job satisfaction, motivation and leadership styles affect the performance of employees at STAIN Batusangkar. This study aims to determine the effect of job satisfaction, motivation and leadership style on employee performance at Sekolah Tinggi Agama Islam Negeri Batusanggkar (STAIN) Batusanggkar.The results of hypothesis testing showed that: (1) there is a positive and significant impact employee job satisfaction on employee performance STAIN Batusanggkar the effective contribution of 6.3 % and 0.047 significance. (2) there is a positive and significant impact employee motivation STAIN Batusanggkar the effective contribution of 21.23 % and a significance of 0.000. (3) there is a positive and significant effect of leadership style on employee performance by employees Batusanggkar effectively 6.5 % and significance of 0.044. (4) there is a positive and significant effect of job satisfaction, work motivation and leadership styles as perceived by employees STAIN Batusanggkar the effective contribution of 50.4 % and a significant 0.000.Kata Kunci: Kepuasan kerja, motivasi, gaya kepemimpinan, kinerja